Quenching molecular photodissociation by intermolecular Coulombic decay - Kopelke, Sören; Chiang, Ying-Chih; Gokhberg, Kirill; Cederbaum, Lorenz S. (The journal of chemical physics, 2012)
In this paper we study the impact of interatomic Coulombic decay (ICD) on molecular photodissociation. The investigation reveals the hitherto unrecognized ability of ICD to quench processes involving nuclear rearrangements. Numerical computations of the nuclear dynamics, initiated by photoexciting the B1Σ+ Rydberg state of CO in CO·Mg complexes, are carried out. The efficiencies of ICD and photoinduced predissociation are compared for the four lowest vibrational levels of the corresponding electronic state. We also show the impact of CO vibrations on the ICD electron spectrum. Finally, we discuss the growing efficiency of ICD to quench the dissociation as the number of neighboring Mg atoms is increased.